2018
DOI: 10.3389/fphys.2017.01126
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Health during Unloading and Reloading Associated with Spaceflight

Abstract: Spinal elongation and back pain are recognized effects of exposure to microgravity, however, spinal health has received relatively little attention. This changed with the report of an increased risk of post-flight intervertebral disc (IVD) herniation and subsequent identification of spinal pathophysiology in some astronauts post-flight. Ground-based analogs, particularly bed rest, suggest that a loss of spinal curvature and IVD swelling may be factors contributing to unloading-induced spinal elongation. In fli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 66 publications
1
33
1
Order By: Relevance
“…Longer periods of severe muscle disuse, as in bedrest, result in changes that are consistent with the significant decrease in mitochondrial content measured in spaceflight [ 17 , 18 , 19 , 20 , 21 ]. The decrease in aerobic capacity significantly affects most of the postural muscles [ 51 ], including the soleus and spinal muscles [ 52 , 53 , 54 ], as opposed to fast muscles such as the deltoid, which shows minimal effects of hypoactivity at the mitochondrial level [ 55 ]. These mitochondrial impairments enhance the muscle atrophy process, leading to muscle deconditioning [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Longer periods of severe muscle disuse, as in bedrest, result in changes that are consistent with the significant decrease in mitochondrial content measured in spaceflight [ 17 , 18 , 19 , 20 , 21 ]. The decrease in aerobic capacity significantly affects most of the postural muscles [ 51 ], including the soleus and spinal muscles [ 52 , 53 , 54 ], as opposed to fast muscles such as the deltoid, which shows minimal effects of hypoactivity at the mitochondrial level [ 55 ]. These mitochondrial impairments enhance the muscle atrophy process, leading to muscle deconditioning [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aging and muscle-wasting diseases have shown a relationship between muscle strength and fat infiltration of muscle (Jones et al, 1983; Liu et al, 1993; Ryan and Nicklas, 1999; Goodpaster et al, 2001; Visser et al, 2002). Investigations into the fat content of neck muscles as well as curvature and intervertebral disc changes may help explain the persistence of herniated nucleus pulposus risk despite preserved muscle size (Johnston et al, 2010; Bailey et al, 2018; Green and Scott, 2018). While MFI was included in this analysis, none of the changes with spaceflight were found to be significant.…”
Section: Discussionmentioning
confidence: 99%
“…The immediate risk of disc herniation upon return from mission is even higher; astronauts are 35.9 times more likely to experience a herniation during the first year post-flight (Johnston et al, 2010). Recent studies have found an association between spinal muscle atrophy and decreased lumbar lordosis that can lead to disc herniation (Bailey et al, 2018; Green and Scott, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to microgravity during spaceflight provokes rapid adaptation in lumbar spine morphology (for review, see (24)). Increased spinal length, loss of lumbar lordosis, vertebral osteopenia, and atrophy of the lumbar multifidus (LM) at L4 and L5 vertebral levels have been observed following space missions (4,11,30).…”
Section: Introductionmentioning
confidence: 99%